Manifestasi Hepatik sebagai Prediktor Mortalitas COVID-19 pada Anak - Suryadi N.N Tatura; Meliana Sulistio (Universitas Sam Ratulangi, 2024)
Abstract: Coronavirus disease-19 (COVID-19) has been associated with hepatic involvement in children, often manifesting as elevated serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels during infection. Some retrospective cohorts and case series have shown various degrees of ALT/AST elevation in with a worse disease’s outcome. Yet, the mechanism was still unknown. This study aimed to determine the association of liver involvement with the outcome of COVID-19 infection in infants and children. This was a prospective and observational study. Subjects were 96 infants and children with confirmed COVID-19 at Prof. Dr. R. D. Kandou Hospital from 1 until 31 January 2022. Patient with pre-existing liver diseases or other infections like malaria and hepatitis, were excluded. The results showed that most respondents were aged between 0 days to 17 years; 75.0% had not any comorbidities. The analysis showed that most subjects with normal ALT levels had a survived outcome (97.5%), while most subjects with abnormal ALT levels had a demise outcome (32.1%). However, about 91.5% of the subjects with normal AST levels had a survived outcome. There was a statistically significant relationship between the elevated of ALT (p=0.006) and of AST (p=0.047) variables with the outcome of infants and children with COVID-19 infection. In conclusion, liver enzyme test is a potential parameter for predicting the mortality of pediatric patients with COVID-19. Keywords: COVID-19; pediatric patients; transaminase enzymes; mortality predictor Abstrak: Kasus Coronavirus disease-19 (COVID-19) pada populasi anak sering dikaitkan dengan manifestasi pada hepar, yang ditandai dengan peningkatan enzim alanin aminotransferase (ALT) dan aspartat aminotransferase (AST). Studi-studi observasional maupun laporan kasus sebelumnya telah menghubungkan manifestasi hepar pada infeksi SARS-CoV-2 dengan luaran penyakit yang lebih buruk, namun mekanisme dibalik keterlibatan hepar tersebut belum dapat dipastikan. Penelitian ini bertujuan untuk mengetahui hubungan antara keterlibatan hepar terhadap luaran mortalitas penyakit COVID-19 pada anak. Jenis penelitian ialah prospektif dan observasional. Subyek penelitian ialah 96 bayi dan anak yang terkonfirmasi COVID-19 di RSUP Prof. Dr. R. D. Kandou selang 1-31 Januari 2022. Pasien dengan riwayat penyakit hepar sebelumnya atau memiliki tanda-tanda infeksi akut hepar, seperti malaria dan hepatitis, dieksklusi dari studi ini. Hasil penelitian mendapatkan subjek didominasi anak usia 0-17 tahun; 75% tidak memiliki komorbiditas. Pada kelompok dengan luaran hidup, mayoritas (97,5%) memiliki nilai ALT normal, sebaliknya pada kelompok dengan luaran meninggal, 32,1% memiliki nilai ALT meningkat. Terdapat hubungan bermakna antara peningkatan kadar ALT (p=0,006) dan AST (p=0,047) terhadap luaran penyakit COVID-19. Simpulan penelitian ini ialah kadar enzim transaminase hepar dapat menjadi salah satu parameter dalam memrediksi luaran mortalitas anak yang terkonfirmasi COVID-19. Kata kunci: COVID-19; pasien anak; enzim transaminase hepar; prediktor mortalitas